2016
DOI: 10.2174/1389202917666151116212901
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma reesei CRE1-mediated Carbon Catabolite Repression in Response to Sophorose Through RNA Sequencing Analysis

Abstract: Carbon catabolite repression (CCR) mediated by CRE1 in Trichoderma reesei emerged as a mechanism by which the fungus could adapt to new environments. In the presence of readily available carbon sources such as glucose, the fungus activates this mechanism and inhibits the production of cellulolytic complex enzymes to avoid unnecessary energy expenditure. CCR has been well described for the growth of T. reesei in cellulose and glucose, however, little is known about this process when the carbon source is sophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 64 publications
0
40
0
8
Order By: Relevance
“…In addition, Antoniêto et al ( 2014 ) showed that in the Δ cre1 mutant strain the expression of amino acid transporters was induced in the presence of cellulose. In addition, during growth in sophorose, expression of the amino acid transporter in the Δ cre1 mutant strain was also induced, indicating that CRE1 acts to inhibit these genes (Antoniêto et al, 2016 ). Similarly, our results pointed to the downregulation of amino acid transporters in sophorose-grown cultures in the Δ xyr1 mutant strain, as well as in cellulose.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Antoniêto et al ( 2014 ) showed that in the Δ cre1 mutant strain the expression of amino acid transporters was induced in the presence of cellulose. In addition, during growth in sophorose, expression of the amino acid transporter in the Δ cre1 mutant strain was also induced, indicating that CRE1 acts to inhibit these genes (Antoniêto et al, 2016 ). Similarly, our results pointed to the downregulation of amino acid transporters in sophorose-grown cultures in the Δ xyr1 mutant strain, as well as in cellulose.…”
Section: Discussionmentioning
confidence: 99%
“…The complex network that coordinates holocellulases expression in T. reesei is also under regulation of nutritional variability. Therefore, differential gene expression was discussed by Castro et al (2014b) and Antoniêto et al (2016) in studies that reported the influence of carbon source on holocellulases transcription. Robust techniques like RNA sequencing have already highlighted the importance of sugar availability on the regulation mediated by TFs in T. reesei (Castro et al, 2016), evidencing the growing need of elucidating deep layers of regulation in this fungus.…”
Section: Introductionmentioning
confidence: 99%
“…Knockout of ACE1 and RCE1 improved the synthesis of cellulase and xylanase [26,27]. The carbon catabolic repression has been regulated by the negative regulation of CRE1 gene [28]. Transcript data of ACEI, RCE1, and CRE1 of the present study were downregulated in the TA OE-Vel1 strain (Fig.…”
Section: Discussionmentioning
confidence: 67%